L’importanza di chiamarsi Kenchiku. L’eccezione giapponese nella storia dell’architettura - Ciotoli, Giusi; Falsetti, Marco (Opus Incertum, 2025)
This essay explores the role of interdisciplinarity in the history of Japanese architecture, beginning with a broader reflection on its impact throughout the twentieth century. Unlike the West, Meiji-era Japan faced the unprecedented challenge of having to bridge a technological gap of several centuries while simultaneously assimilating cultural paradigms foreign to its architectural tradition. Notably, due to different cultural conditions and the absence of theoretical and didactic manuals, Japan originally lacked a concept directly comparable to that of ‘Architecture’ in the Western sense. This condition was further exacerbated by the prejudiced perspectives of some Europeans who came to teach at Japan’s newly established universities. Their biased interpretations created a sense of inferiority with respect to European architecture, a perception only gradually dismantled through the work of pioneering figures such as Itō Chūta and Bruno Taut. Furthermore, the historiography of Japanese architecture was largely shaped by architects, urban planners, and art historians, rather than by architectural historians, as exemplified by Walter Gropius and Kenzo Tange’s richly illustrated 1960 book, Katsura: Tradition and Creation in Japanese Architecture, which remains a milestone for the discipline.